Cross‐Ancestry Associations of Spontaneous Coronary Artery Dissection Genetic Risk With Coronary Atherosclerosis and Migraine Headache - Chang Xu; Min‐Lee Yang; Pik Fang Kho; Shoa L Clarke; Catherine Tcheandjieu; Patricia A. Peyser; Cathy Shen‐Jang Fann; Shih‐Pin Chen; Jacqueline Saw; Xiang Zhou; Themistocles L. Assimes; Santhi K. Ganesh (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Research studies of spontaneous coronary artery dissection (SCAD) have been primarily focused on European‐ancestry individuals, with limited recognition and investigation in non–European‐ancestry individuals. While SCAD has not been well ascertained in non–European‐ancestry groups, pleiotropic associated traits identified in those of European ancestry have been assessed in individuals of other ancestries. Whether these traits are associated with the complex genetic architecture of SCAD in those of non‐European ancestry has not been previously investigated. Methods We investigated the associations of an established SCAD polygenic score with multiple vascular diseases in ≈900 000 ancestrally diverse participants of large‐scale studies. Individual‐level data from the UK Biobank and the Million Veteran Program and summary statistics of publicly available databases were analyzed. Results A set of associations between SCAD polygenic score and related vascular diseases were replicated in non‐European samples. Notable associations with the SCAD polygenic score included (1) coronary artery disease, myocardial infarction, and migraine headache in a Hispanic group (coronary artery disease: odds ratio [OR], 0.93 [95% CI, 0.90–0.95]; P=2.35×10−7; myocardial infarction: OR, 0.88 [95% CI, 0.80–0.96]; P=5.73×10−3; migraine headache: OR, 1.03 [95% CI, 1.01–1.06]; P=1.86×10−2) of the Million Veteran Program; (2) headache in an African‐ancestry group (OR, 1.22 [95% CI, 1.06–1.41]; P=6.94×10−3) and a South Asian–ancestry group (OR, 1.18 [95% CI, 1.02–1.37]; P=2.43×10−2) of the UK Biobank; and (3) coronary artery disease, myocardial infarction, and migraine headache in East Asian–ancestry cohorts (coronary artery disease: OR, 0.95 [95% CI, 0.93–0.98]; P=2.66×10−3; myocardial infarction: OR, 0.86 [95% CI, 0.83–0.89]; P=9.51×10−16; migraine headache: OR, 1.27 [95% CI, 1.10–1.47]; P=1.03×10−3). Conclusions Pleiotropic associations of SCAD polygenic risk with related vascular diseases previously identified in European‐ancestry groups showed notable, largely consistent patterns in non–European‐ancestry groups.